Species diversity of order Trichoptera (Insecta) in district Abbottabad (Zoo Botanica, 2023)
Caddis flies are important bio indicators of water quality. Present study was planned to explore the species diversity of insect order Trichoptera in section of River Dorr between Harno and Dhamtor of district Abbottabad, Pakistan in 2018. Four sites were selected viz. site A, B, C and D, where site A was upstream while site B, C and D was downstream and a distance of 300 meters in between all four sites. Kicking and hand picking techniques were used. Samples were collected using D-frame kick net. Samples were washed, sorted and preserved in 70% alcohol in plastic bottles. A total of 243 individuals of Trichoptera larvae were sampled belonging to five families (Hydropsychidae, Hydroptilidae, Leptoceridae, Phryganeidae, and Polycentropodidae. Hydropsychidae (37.03%), Hydroptilidae (30.86%) and Leptoceridae (29.21%) were found to be the most abundant families whereas Phryganeidae (2.46%) and Polycentropodidae (0.41%) were least encountered families. Greater species diversity of Trichoptera was observed in early-late March.
Keywords: Trichoptera; larvae; bio indicators; water quality; D-frame kick net